Frequency and Culture Sensitivity of Febrile Neutropenic Episodes in Paediatric Patients of Acute Lymphoblastic Leukemia on Chemotherapy - Saima Akhtar , Bilal Ahmad , Iqtadar Haider Shirazi , Muhammad Tahir , Saba Afzal , Nadeem Ikram (Journal of Rawalpindi Medical College, 2018)
Background: To determine frequency of febrile neutropenia episodes (FN) in patients of acute lymphoblastic leukaemia (ALL) on chemotherapy and to study different type of organisms isolated in them along with their sensitivity to different antibiotics. Methods: In this descriptive study children of either gender diagnosis of ALL and on any one of the initial four phase of chemotherapy including induction, consolidation, interim maintenance and delayed intensification were followed prospectively from start till end of that particular phase. The chemotherapy protocol used in the centre is BFM protocol. Patients who developed fever (≥ 38°C) during this time and turned out to be neutropenic (ANC ≤ 500/mm3) underwent blood culture(on Bectec). Antimicrobial susceptibility profile was done by Kirby Bauer disc diffusion method on Muller Hinton agar, according to CLSI 2006 guidelines. Results: Mean age of children was 5.5(±3.0) years. Of 94 ALL patients enrolled in the current study, 46% were younger than 5 years and 73% were males. Out of 94 37 (39%) developed fever and neutropenia. The mean (SD) temperature of all the children was 38.9 (±0.3)0C. The mean (SD) absolute neutrophil count (ANC) was 264.0 (±149.2)/mm3. Out of 37 children who developed febrile neutropenia, 25% had positive blood cultures. The most common isolate was Klebsiella (44.4%), followed by Pseudomonas aeruginosa (33.3%) and Staphylococcus aureas (22.2%). Klebsiella was sensitive to most of the antibiotics tested except cephalosporins. A sensitivity of Pseudomonas was 100% to ceftazidime and cefotaxime while Staph. aureas was 100% sensitive to ceftazidime, imipenem and ciprofloxacin. Conclusion: Nearly two-fifths of the children with ALL developed febrile neutropenia. A quarter of them showed positive blood cultures. The most common pathogen found in our study was Klebsiella, followed by Pseudomonas and Staphylococcus aureus. Most of the antibiotics tested for the Klebsiella were shown to be effective except cephalosporins. For Pseudomonas, Cefrazidine and Cefotaxime were 100% sensitive, while for Staphylococcus Cefrazidine, Imipenem and Ciprofloxacin showed 100% sensitivity.